2019
DOI: 10.1017/ice.2019.252
|View full text |Cite
|
Sign up to set email alerts
|

Multiple importations and transmission of colistin-resistantKlebsiella pneumoniaein a hospital in northern India

Abstract: Objective:Resistance to colistin, a last resort antibiotic, has emerged in India. We investigated colistin-resistant Klebsiella pneumoniae(ColR-KP) in a hospital in India to describe infections, characterize resistance of isolates, compare concordance of detection methods, and identify transmission events.Design:Retrospective observational study.Methods:Case-patients were defined as individuals from whom ColR-KP was isolated from a clinical specimen between January 2016 and October 2017. Isolates resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…28 As the network grows and receives more data, it can eventually produce representative data for comparisons and benchmarking of facility-level performance. To date, several outbreaks have been identified and contained through use of data from the surveillance network, including an outbreak of colistinresistant Klebsiella pneumoniae in network hospitals 29 and a large outbreak of bloodstream infections caused by Burkholderia cepacia. 30 There are at least seven limitations to the data generated by the surveillance network.…”
Section: Table 5: Commonly Reported Pathogens In Bloodstream Infectio...mentioning
confidence: 99%
“…28 As the network grows and receives more data, it can eventually produce representative data for comparisons and benchmarking of facility-level performance. To date, several outbreaks have been identified and contained through use of data from the surveillance network, including an outbreak of colistinresistant Klebsiella pneumoniae in network hospitals 29 and a large outbreak of bloodstream infections caused by Burkholderia cepacia. 30 There are at least seven limitations to the data generated by the surveillance network.…”
Section: Table 5: Commonly Reported Pathogens In Bloodstream Infectio...mentioning
confidence: 99%
“…Where they have reported the incidence of ColR-KP infection at 46.4% and 33.3% respectively. However, contemporary Indian studies have reported colistin resistance in Klebsiella ranging from 4% [17], to 5.6% [8], but the relative number of cases was very less.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, 35 studies (83.3%) restricted attempts to identify transmission routes to the same hospital unit during a defined period. 9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][29][30][31][32][33][34][35][36][37][38][40][41][42][44][45][46][47] Only 7 studies (16.7%) examined other possible routes such as medical procedures or healthcare workers. [3][4][5]10,28,39,43 Several studies were notable for uncovering otherwise unidentified transmissions, which is the main goal of WGS surveillance.…”
Section: Resultsmentioning
confidence: 99%